Synthesis of Novel Hydrogels based Poly(4-Hydroxyphenylazo-3-N-(4-hydroxyphenyl)maleimide) for Specific Colon Delivery of Chemotherapeutic Agent - P. Rama Subba Reddy, K.S.V. Krishna Rao & , K. Madhusudana Rao, N. Sivagangi Reddy (Journal of Applied Pharmaceutical Science, 2015)
In recent years azo functionalized polymeric hydrogels are very interesting; it is due to their promising applications in various fields especially in the colon drug delivery. 4-Hydroxyphenylazo-3-N-(4-hydroxyphenyl) maleimide (HPM) was synthesized and used for development of hydrogels by free radical polymerization with acrylamide (Am) and N,N-methylene bis acrylamide. Synthesized poly(Am-co-HPM) (PAH) hydrogels were used for encapsulation of 5-fluorouracil (5-FU) an anticancer drug. Structural, thermal, morphological and drug distribution of PAH hydrogels were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy and X-ray diffraction techniques, respectively. Maximum percentage of encapsulation efficiency i.e. 78.25±1.3 was observed for AZ1 PAH hydrogels. 5-FU release studies were performed by in vitro method in simulated gastro intestinal fluids (pH 1.2 & 7.4). To support the 5-FU release mechanism from PAH hydrogels, swelling and deswelling kinetics were studied in doubly distilled water.
Keywords: Hydrogels, Azo compounds, 5-Fluorouracil, Colon, Drug Delivery.